Detection of Copy Number Variation (CNV) and its characterization in Brazilian population - Ciconelle, Ana Cláudia Martins (2018)
Genome-wide association studies (GWAS) are a tool of high importance to associate genetic markers, genes and genomic regions with complex phenotypes and diseases, allowing to understand in details this regulation of gene expression as well as the genes, and then develop new techniques of diagnoses and treatment of diseases. Nowadays, the main genetic marker used in GWAS is the SNP (single nucleotide polymorphism), a variation that affects only one base of the DNA, being the most common type of variation between individuals and inside the genome. Even though there are multiple techniques available for GWAS, several complex traits still have unexplained heritability. To contribute to these studies, reference genetic maps are being created, such as the HapMap and 1000 Genomes, which have common genetic variants from world wide population (including European, Asian and African populations). In the last years, two solutions adopted to solve the missing heritability are to use different types of genetic variants and include the rare and population specific markers. Copy number variation (CNV) is a structural variant which use is increasing in GWAS in the last years. This variant is characterized for the deletion or duplication of a region a DNA and its length can be from few bases pair to the whole chromosome, as in Down syndrome. In collaboration of the Heart Institute (InCor-FMUSP), this work uses the dataset from Baependi Heart Study to establish a methodology to characterized the CNVs in the Brazilian population using SNP array data and associate them with height. This project uses the genetic and phenotype data of 1,120 related samples (family structure). For CNV calling, resources from the software PennCNV are used and methodologies of preprocessing, normalization, identification and other analysis are reviewed. The characterization of CNVs include information about location, size, frequency in our population and the patterns of inheritance in trios. The association of CNVs and height is made using linear mixed models and with information of family structure. The obtained results indicate that the Brazilian population has regions with variation in the number of copies that are not in the literature. General characteristics, such as length and frequency in samples, are similar to the information found in the literature. In addition, it was observed that the transmission of CNVs could not follow the Mendelian laws, since the frequency of trios which one parent has a deletion/duplication and the offspring is normal is higher than the frequency of trios with one parent and the offspring has a deletion/duplication. This work also identified a region on chromosome 9 that could be associated to height, being that carries of a duplication in this region can have the expected height dropped by approximately 3cm.